Answer:
B (-2 , -11)
Step-by-step explanation:
hello : the system is :
y = 4x - 3
y= -x - 13
put x = -2
y = 4(-2) - 3=- 11
y= -(-2) - 13 = -11
Formula:
a^2+b^2=c^2
c^2: Is the hypotenuse.
For a^2 and b^2, you have to multiply both it by its self.
Then, add both.
Next, you square root it.
Example:
a^2+b^2=c^2
14^2+7^2=c^2
196+49=c^2
245=c^2
15.64=c^2
Just get the app photo math it tells you the answer to go math math books and more
Add the equations,just the way they appear there.
-- Add the top 'x' to the bottom 'x'. Write the sum under the 'x's.
-- Add the '+y' and the '-y'. Write the sum under the 'y's.
-- Add the '2' and the '4'. Write the sum under them, with n " = " sign
before it.
You should now have an equation with only 'x' in it and no 'y'.
You can easily solve that one and find out the value of 'x'.
Once you know the value of 'x', go back to either one of the original
equations, and plug the number-value of 'x' in place of 'x'.
You'll then have an equation with only 'y' in it and no 'x'.
You can easily solve that one and find out the value of 'y'.
Answer:
The responses to the given can be defined as follows:
Step-by-step explanation:
For point a:
fixing probability vector that is
relation:
solving the value:
Therefore the stationary distribution
For point b:
will be limiting distribution if
satisfies the above condition so, it is limiting the distribution.